Optimizing donor tooth selection for autotransplantation in the anterior maxilla via CBCT‐based root width and crown‐root angle measurements - Companioni, Stephanie; Nguyen, Tung; Divaris, Kimon; Christensen, John (Dental traumatology, 2023)
Background/Aim The clinical management of growing patients with missing teeth in the anterior maxilla can be challenging due to limited treatment options and high esthetic demands. Tooth autotransplantation (AT) is a viable option for these cases. The selection of donor teeth has been reported to be driven by root development, existing malocclusion, and esthetics. The aim of this study was to add to the evidence base of tooth selection criteria for AT by examining candidate donor teeth root width and crown‐root angles, two factors arguably important for surgical planning and esthetics. Material and Methods Cementoenamel junction (CEJ) tooth width and crown‐root angle measurements were made using cone‐beam computed tomography (CBCT) images of 30 children and adolescents of European descent (mean age = 13 years, range = 10–17 years; 63% male) from a private orthodontic practice. Measurements of maxillary central and lateral incisors (index teeth) were compared with measurements of maxillary second premolars, mandibular central incisors, and mandibular first and second premolars (candidate donor teeth). Analyses relied on descriptive statistics of mean within‐subject differences between index and donor teeth and the proportion of individuals without clinically important differences (i.e., >1.5 mm width deficit and > 15 degrees crown‐root angle difference). Results Mandibular first premolars were the most compatible teeth for the replacement of maxillary central incisors based on both width (≥97% of individuals) and angle measurements (≥87% of individuals), followed closely by mandibular second premolars. Mandibular central incisors were the most compatible for the replacement of maxillary laterals, among all individuals based on width and ≥ 90% based on angle, whereas mandibular first premolars were somewhat less compatible. Conclusions The study offers evidence of within‐person, CBCT‐based root width dimension and crown‐root angle compatibilities. This information can be considered in addition to existing tooth selection criteria for AT including Angle's classification, midline deviation, crowding severity, root development, and esthetics.